Diastereoselective Synthesis of Pyrazolines by Metal-Free Rearrangement of Bicyclic Triazolines - Bucci, Raffaella; Clerici, Francesca; Pellegrino, Sara; Erba, Emanuela (Synthesis, 2020)
The metal-free preparation of diazoalkanes through the ring rearrangement of bicyclic triazolines is reported here. Their use in 1,3-dipolar cycloaddition reactions with electron-withdrawing alkenes was investigated. This synthetic procedure allows differently substituted pyrazolines to be obtained in few steps and with high atom economy.
Keywords: diazoalkanes; pyrazolines; amidines; 1,3-dipolar cycloaddition; triazoline rearrangement; metal-free reactions; diastereoselectivity; atom economy